Art, elitism, authenticity and liberty navigating paradox - Clements, Paul 1959- (Routledge, Taylor & Francis Group, 2025)
"This book excavates the depths of creative purpose and meaning-making, and the extent to which artist autonomy and authenticity in art is a struggle against psychological conditioning, controlling cultural institutions and markets, key to which is representation. The chapters are underpinned by examples from the arts and the narrative weaves a trail through a range of conceptualizations which are applied to various aspects of visual culture from mainstream canonical arts to avant-garde, community and public art; social and political art to commercial art; ethereal art to the popular, edgy and kitsch. The book is wide-ranging and employs various aesthetic, cultural, philosophical, political, psycho-social, and sociological debates to highlight the problems and contradictions that an encounter with the arts and creativity engenders. The book will be of interest to scholars working in art history, museum studies, arts management, cultural policy, cultural studies and cultural theory"--
Keywords: Arts and society; Arts et société